Upaya Peningkatan Pendapatan Keluarga Tani Teh Rakyat melalui Pemberdayaan Wanita Pedesaan di Kecamatan Cisurupan Kabupaten Garut - Lucyana Trimo; Syarif Hidayat; Muhammad Arief Budiman (Jurnal Pengabdian Pada Masyarakat, 2020)
EFFORTS TO INCREASE INCOME OF PEOPLE'S TEA FARMERS’ FAMILIES THROUGH EMPOWERING RURAL WOMEN IN CISURUPAN DISTRICT, GARUT REGENCY. To increase the family income of tea smallholder, the participation of wives as housewives in the community tea smallholder is very important. Considering that there is still a lot of free time they have; and also their habits in doing food processing, so if they are fostered in earnest, their potential can be developed into a form of productive business. This can automatically increase its role in increasing the income of the household concerned. In the end, the welfare of farmer households (in particular) can also be improved. The method used in the implementation of Community Service is PRA (Participatory Rural Appraisal), a method whose purpose is to find a shared solution, and the goal is, the Khasanah Business Group which is a pilot group in Kampong of Ciela, Sirnajaya Village, Cisurupan District, Garut Regency. In Community Service Activities, product innovation has been developed, rehabilitation of production equipment, provision of business management materials and market development of processed products from the Khasanah Business Group through KKN students who are interested in acting as marketing channels in the campus and surrounding areas. In addition, to increase public confidence in the products of the Khasanah Business Group, assistance has been made to arrange the making of PIRT letters (Household Industrial Products) by students involved in KKN. Furthermore, so that the Khasanah Business Group can develop its business to the fullest, then continuous guidance is needed, namely through mentoring activities, so that the Khasanah Business Group can run better which ultimately can manage their business independently.